Physical Properties of Cellulose Derivative-Based Edible Films Elaborated with Liposomes Encapsulating Grape Seed Tannins - Constanza Vidal; Johana Lopez-Polo; Fernando A. Osorio (MDPI AG, 2024)
Combined use of edible films (EF) with nanoencapsulation systems could be an effective alternative for improving the films' physical properties and maintaining bioactive compounds' stability. This research work focuses on the combined use of EF of cellulose-derived biopolymers enriched with liposomes that encapsulate grape seed tannins and on the subsequent evaluation of the physical properties and wettability. Tannin-containing liposomal suspensions (TLS) showed 570.8 ± 6.0 nm particle size and 99% encapsulation efficiency. In vitro studies showed that the release of tannins from liposomes was slower than that of free tannins, reaching a maximum release of catechin of 0.13 ± 0.01%, epicatechin of 0.57 ± 0.01%, and gallic acid of 3.90 ± 0.001% over a 144 h period. Adding liposomes to biopolymer matrices resulted in significant decrease (p < 0.05) of density, surface tension, tensile strength, elongation percentage, and elastic modulus in comparison to the control, obtaining films with greater flexibility and lower breaking strength. Incorporating TLS into EF formulations resulted in partially wetting the hydrophobic surface, reducing adhesion and cohesion compared to EF without liposomes. Results indicate that the presence of liposomes improves films' physical and wettability properties, causing them to extend and not contract when applied to hydrophobic food surfaces.